An Experimental Study of the Ant Colony System for the Period Vehicle Routing Problem - Matos, Ana Cristina (2017)
In this paper, a new Ant System approach to the Period Vehicle Routing Problem (PVRP) is presented. In PVRP, visit days have to be assigned to customers in order to find efficient routes over the period. We suggest a new technique for defining the initial solution and a novel strategy to update the pheromone trails that is especially suited for solving large scale problems. An illustrative example for a waste collection system involving 202 localities in the municipality of Viseu, Portugal, demonstrates the effectiveness of the model.